Penerapan Sistem Kearsipan Dalam Meningkatkan Kelancaran Proses Administrasi Kerja Pegawai Pada Bagian SDM Dan Administrasi Di PT PLN (Persero) UP3 Samarinda - Muhammad Nawawi; Besse Asniwaty; Anna Tasiyah (Politeknik Negeri Samarinda, 2020)
Archiving activities are important for a company or agency, because archiving itself has a function as a source of memory, a source of information, and material for making decisions, for that, archiving needs to be managed and handled properly and appropriately. The focus of the problem in this research is how the application of filing systems in the human resources and administration at PT. PLN (Persero) UP3 Samarinda. The purpose of this study was to determine the Application of Filing Systems in the HR and Administration section of PT. PLN (Persero) UP3 Samarinda. The data collection techniques used by the writer are observation and literature study. While the analysis used is descriptive analysis, which describes an object at a time. The results of this study indicate that the archival management system in the HR and Administration section at PT. PLN (Persero) UP3 Samarinda uses a subject system and a chronological system. However, in terms of management and storage, it is still lacking, because when looking for an archive it must take quite a long time. In addition, the problem that the author experienced was that the information in the ordner was not written in the year corresponding to the year in the letter. The ordner storage is also not neatly ordered. It is recommended that the company provide special training for employees regarding archiving in order to pay more attention to the existing archives at PT. PLN (Persero) UP3 Samarinda, starting from its creation to its destruction.